2013
DOI: 10.1590/0074-0276130112
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a chemiluminescent enzyme-linked immunosorbent assay for the diagnosis of Trypanosoma cruzi infection in a nonendemic setting

Abstract: The disappearance of lytic, protective antibodies (Abs) from the serum of patients with Chagas disease is accepted as a reliable indicator of parasitological cure. The efficiency of a chemiluminescent enzyme-linked immunosorbent assay based on a purified, trypomastigote-derived glycosylphosphatidylinositol-anchored mucin antigen for the serologic detection of lytic Abs against Trypanosoma cruzi was evaluated in a nonendemic setting using a panel of 92 positive and 58 negative human sera. The technique proved t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 21 publications
1
17
0
3
Order By: Relevance
“…Although O -glycans of GPI-mucins from the insect-derived parasite forms have been well characterized in several parasite strains and genotypes, the exact structural information of most O -glycans for the mammal-dwelling tGPI-mucins remains unknown. Partial structural analysis and immunoassays have revealed that many of these trypomastigote-derived GPI-mucin (tGPI-mucin) O -glycans contain a terminal α-Gal residue, which is non-reducing and conserved on tGPI-mucins from at least four major Chagas disease causing T. cruzi genotypes [15, 60, 61]. These tGPI-mucin glycans are predominantly branched, and highly heterogeneous with different connectivities of the terminal α-Gal moiety to another sugar unit [12, 62].…”
Section: Resultsmentioning
confidence: 99%
“…Although O -glycans of GPI-mucins from the insect-derived parasite forms have been well characterized in several parasite strains and genotypes, the exact structural information of most O -glycans for the mammal-dwelling tGPI-mucins remains unknown. Partial structural analysis and immunoassays have revealed that many of these trypomastigote-derived GPI-mucin (tGPI-mucin) O -glycans contain a terminal α-Gal residue, which is non-reducing and conserved on tGPI-mucins from at least four major Chagas disease causing T. cruzi genotypes [15, 60, 61]. These tGPI-mucin glycans are predominantly branched, and highly heterogeneous with different connectivities of the terminal α-Gal moiety to another sugar unit [12, 62].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have also proposed a chemiluminescent ELISA (CL-ELISA) with purified trypomastigote glycoproteins for the detection of lytic protective antibodies against T. cruzi in human serum (33,51,52). CL-ELISA achieved high diagnostic accuracy in both areas that are endemic (51,52) and nonendemic (33) for the disease. Detection systems, such as chemiluminescence, increase light amplification and signal duration in comparison with traditional ELISAs.…”
Section: Discussionmentioning
confidence: 99%
“…Inconclusive or equivocal results were determined by a titer between 0.9 and 1.0. [ 27 , 35 ]All sera were tested in duplicate and the results were expressed as the mean of two simultaneous determinations.…”
Section: Methodsmentioning
confidence: 99%